Effect of ART2 on the CD4 count and viral load during treatment of second line ART - Singh, Narendra; Varma, R. K.; Giri, Richa; Varma, Punit; Dwivedi, Seema; Kumar, Lalit (International Journal of Advances in Medicine, 2020)
Background: AIDS first recognized in US summer of 1981 by the U.S. CDC reported. In 1983 HIV was isolated from a patient of lymphadenopathy. This study was for monitoring the change in CD4 count and viral load of PL HIV before and after one year of second line ART in the period of 2016 to 2018. Methods: Study was single centre hospital based and clinical continuous longitudinal, prospective and retrospective, observational at ART plus Centre, Kanpur K.P.S. Institute of Medicine (G.S.V.M. medical college Kanpur) included the all patients on ART1 attending in centre were screened for treatment failure based on clinical, immunological and virological criteria’s as decided by SACEP from 2016 to 2018. Results: CD4 count at the time of initiation that of second line ART, there is low CD4 count the mean value is 181.44±85.02 in total subject 118 but 12 month of second line ART 2 treatment mean value of CD4 count 413.01±168.70. After Z test application the value is 13.316, p value 0.0001, MD 231.5, CI is 95%.Viral load value at time of start of second line ART mean value is 80683.85849±293449.2038, after 1 to 12 month of start of second line ART treatment mean value is 350.8559±128.1069, for this Z value is 2.972, p value 0.0033. Conclusions: Second line ART is most effective in treatment after failure with first line ART. CD 4 count increase and viral load decrease and clinical feature improve after treatment of ART 2.